Kinematic gait deficits at the trunk and pelvis: characteristic features in children with hereditary spastic paraplegia. (22nd February 2016) - Adair, Brooke; Rodda, Jillian; McGinley, Jennifer L; Graham, H Kerr; Morris, Meg E
Abstract : Aim: To examine the kinematic gait deviations at the trunk and pelvis of children with hereditary spastic paraplegia (HSP). Method: This exploratory observational study quantified gait kinematics for the trunk and pelvis from 11 children with HSP (7 males, 4 females) using the Gait Profile Score and Gait Variable Scores (GVS), and compared the kinematics to data from children with typical development using a Mann–Whitney U test. Results: Children with HSP (median age 11y 4mo, interquartile range 4y) demonstrated large deviations in the GVS for the trunk and pelvis in the sagittal and coronal planes when compared to the gait patterns of children with typical development ( p =0.010–0.020). Specific deviations included increased range of movement for the trunk in the coronal plane and increased excursion of the trunk and pelvis in the sagittal plane. In the transverse plane, children with HSP demonstrated later peaks in posterior pelvic rotation. Interpretation: The kinematic gait deviations identified in this study raise questions about the contribution of muscle weakness in HSP. Further research is warranted to determine contributing factors for gait dysfunction in HSP, especially the relative influence of spasticity and weakness. What this paper adds: Important hereditary spastic paraplegia (HSP) kinematic deficits were identified at the trunk/pelvis. Deviations included increased ranges of movement in the sagittal/coronal planes. Kinematics for the transverse plane showed little deviation from normal. Muscle weakness may contribute to gait patterns in HSP. This article is commented on by Ounpuu on pages790–791 of this issue.